2020
DOI: 10.1016/j.najef.2020.101244
|View full text |Cite
|
Sign up to set email alerts
|

Current account and credit growth: The role of household credit and financial depth

Abstract: Understanding the impact of financial variables on the current account balance is one of the priorities of academic literature and policy makers. Evidence from a broad panel of countries shows that an increase in the credit growth causes a significant deterioration in the current account balance. We find that this result is driven by household credit. Furthermore, we show that total and household credit growth rates have a stronger negative effect on the current account balance for lower levels of financial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In addition, excessive lending can lead to a significant deterioration of the current account balance. Thus, Ekinci and Omay clarified that the growth rates of total lending and lending to households, in contrast to the growth of corporate lending, have a more substantial negative effect on the current account balance at a low level of financial depth [30]. This is consistent with the statement of the too much finance hypothesis.…”
Section: Benefits and Drawbacks Of Financial Deepeningsupporting
confidence: 71%
“…In addition, excessive lending can lead to a significant deterioration of the current account balance. Thus, Ekinci and Omay clarified that the growth rates of total lending and lending to households, in contrast to the growth of corporate lending, have a more substantial negative effect on the current account balance at a low level of financial depth [30]. This is consistent with the statement of the too much finance hypothesis.…”
Section: Benefits and Drawbacks Of Financial Deepeningsupporting
confidence: 71%
“…Similarly, Koong et al (2017) explored relations between credit expansion and financial stability in Malaysia and conjectured that business credit growth had an adverse impact on financial stability, while it was not confirmed that an increase in household credit had a similar effect. Interestingly, a recent study of advanced and emerging economies by Ekinci and Omay (2020) found the contrary. Particularly, an increase in household credit growth led to notable deterioration in the current account balance, with more profound effect for the countries with lower levels of financial depth, while such relation was not identified for business loans.…”
Section: Literature Reviewmentioning
confidence: 87%
“…About the impact of household finance on the macroeconomy, Zhang (2019) established a DSGE model with household debt and concluded that changes in housing demand and negative shocks to risk perceptions in the real estate industry would lead to lower bank net worth, higher deposit and loan spreads, lower investment, and economic downturn [6] . Research by Ekinci (2020) shows that household credit leads to a decline in current account balances, proving the macroeconomic impact of household financial behavior [7] .…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%